2008
DOI: 10.1016/j.tcm.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Proteasome Assembly and Regulation: Importance to Cardiovascular Medicine

Abstract: The cardiac proteasome is increasingly recognized as a complex, heterogeneous and dynamic organelle contributing to the modulation of cardiac function in health and diseases. The emerging picture of the proteasome system reveals a highly regulated and organized molecular machine integrated into multiple biological processes of the cell. Full appreciation of its cardiovascular relevance requires an understanding of its proteolytic function as well as its underlying regulatory mechanisms; of which assembly, stoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In this investigation and previous studies from our group (10,11,9) we have identified phosphorylation, N-terminal acetylation, myristoylation, and arginine and lysine methylation of proteasome subunits. These results were validated with a combined approach using mass spectrometry and immunoblotting with specific antibodies.…”
Section: Discussionmentioning
confidence: 56%
“…In this investigation and previous studies from our group (10,11,9) we have identified phosphorylation, N-terminal acetylation, myristoylation, and arginine and lysine methylation of proteasome subunits. These results were validated with a combined approach using mass spectrometry and immunoblotting with specific antibodies.…”
Section: Discussionmentioning
confidence: 56%
“…[23][24][25][26][27] Cardiac proteasomes contribute to the modulation of cardiac function in health and disease. 28 However, apart from the reported observation that IPs are expressed in the myocardium in acute CVB3 myocarditis, their functional impact has not been studied so far. 10 The present study focuses on IFN-induced myocardial IP activity in CVB3 myocarditis.…”
Section: Murine Models Of Coxsackievirus B3 (Cvb3)mentioning
confidence: 99%
“…Relative affinity (RA) of peptides to MHC class I and stability (DC50) of MHC class I ligands complexes were determined as described elsewhere. 28 For affinity studies, stripped RMA-S cells were incubated with various peptide concentrations (100.0, 50.0, 5.0, 2.5, 0.5 g/ml) overnight in serum-free medium supplemented with 1.5 g/ml ␤2 microglobulin. For MHC class I stability, RMA-S cells were incubated with 100 g/ml peptide overnight, washed, and cultured in the presence of brefeldin A for 0, 2, 4, 6, and 8 hours.…”
Section: Mhc Binding Characteristics Of Vp2 [285-293] (Frhnnvtlm) Of mentioning
confidence: 99%
“…[75][76][77] In fact, the mammalian cardiac proteasome is molecularly heterogeneous, 78 and its functional regulation differs from proteasomes in other tissues and from yeast cells. 79 This relates mainly to tissue specific expression of several proteasome components (eg, an alternatively spliced isoform of Rpn10 within the 19S complex). 76 A recent study by Kloss et al 80 has classified different proteasomal subpopulations based on their susceptibility to proteasome inhibitors, categorizing rat heart proteasomes into their spectrum of subtypes.…”
Section: Cardiac-specific Proteasomesmentioning
confidence: 99%